Działalność proinnowacyjna jako czynnik sukcesu przedsiębiorstwa - ujęcie teoretyczno-empiryczne - Glabiszewski, Waldemar (Pro-Innovative Activity as the Factor Influencing Enterprise Success - Theoretical and Empirical Approach, 2008)
The paper is of theoretical and empirical character. The theoretical part is an attempt to point out the role of company's pro-innovative activity for its market success. The empirical part of the paper presents the research findings concerning different signs of proinnovative activities undertaken by enterprises of Kujawsko-pomorskie region. Moreover, this part of the paper identifies some innovative undertakings of analysed companies and also their results which may be important sources of the competitive advantage.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 75-83